The Swings of Selendang: a Deconstruction Point of View of Tohari’s Ronggeng Dukuh Paruk (The Dancer) - Fajarini, Suzana Maria L.A. (Journal of Language and Literature, 2017)
Employing different perspectives will result on different meanings of a scarf (selendang – Javanese/Indonesian) in Ronggeng Dukuh Paruk (The Dancer). Known as an adornment and beautification for women in dancing costume, a scarf represents the shackle of the dancer, Srintil as the protagonist in the novel. In the different point of view, the same scarf can be a symbol of Srintil’s dominance against the patriarchal system. The novel itself shows subjugation towards women done by patriarchal system. Believed to be born as a ronggeng dancer, Srintil goes through oppressions since her early adolescent. However, employing Derrida’s deconstruction theory, this paper will argue that Srintil attempts very hard to achieve her liberation and to overturn the control. The swings of the scarf during the dancing denote the domination of the dancer’s fated life and her self-determination as a woman. Under a strong influence of Javanese female negotiation, Srintil endeavors to liberate herself – although she is rendered to be unsuccessful – yet, there are some efforts done by her. Through some discussion the readers are supposed to observe that Srintil – who is treated unjustly by patriarchal society – manipulatively resists and fights for her freedom.Keywords: deconstruction, patriarchal system, subjugation, resistence